The Black Count [compact disc, unabridged] : glory, revolution, betrayal, and the real Count of Monte Cristo - Reiss, Tom (Books on Tape : Random House Audio, 2012)
He was only 32 when he was given command of 53,000 men, the reward for series of triumphs that many regarded as impossible, and then topped his previous feats by leading a raid up a frozen cliff face that secured the Alps for France. It was after his subsequent heroic service as Napoleon's cavalry commander that Dumas was captured and cast into a dungeon, and a harrowing ordeal commenced that inspired one of the world's classic works of fiction.